(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article provides a diagram and constructional peculiarities of a chain drive with a composite driven sprocket and a composite roller in the transmission mechanisms of technological machines. The regularities of the driven sprocket shafts movement, as well as the noise indicators of the compared chain drives are presented. Based on the analysis of the obtained experimental results, the main parameters of the recommended chain transmission with elastic elements were substantiated.